Vulnerability of elderly people during climate-induced disasters in Sub-Saharan Africa: a scoping review - Matlakala, Frans Koketso; Rantho, Katlego Magdeline; Mapaling, Curwyn (Frontiers in Human Dynamics, 2024)
Climate-induced disasters present significant challenges to vulnerable populations, especially elderly individuals with disabilities who face unique difficulties in preparing for, responding to, and recovering from such catastrophic events. Despite growing concerns about the impact of climate-induced disasters in sub-Saharan Africa, there is a notable lack of information regarding the specific vulnerabilities experienced by elderly people with disabilities in this region. This study aims to address this gap by identifying and synthesising the existing literature on the subject. Researchers conducted a scoping review, selecting articles from regional (Sabinet African Journals, Science Direct) and global databases (PubMed, PsycINFO, and ProQuest) using search strategies with Boolean operators, truncations, and MeSH terms.The review included primary studies (qualitative, quantitative, and mixed methods) published between 2013 and 2023 that met specified inclusion and exclusion criteria, with a focus on assessing the quality of the included studies. The findings revealed that elderly people in sub-Saharan Africa face significant physical, cognitive, and socio-economic challenges due to limited access to resources, inadequate infrastructure, and social exclusion. These challenges are amplified in the sub-Saharan context, highlighting a critical gap in inclusive risk reduction strategies during disasters. The review emphasises an urgent need for targeted research and the development of community-based intervention programmes to improve the resilience and wellbeing of elderly individuals with disabilities facing climate-induced disasters. This study not only mapped the existing literature but also underscored the scarcity of research in the field of climate-induced disasters, with only six articles focusing on the elderly. The researchers recommend the development of more inclusive disaster risk reduction strategies and policies.